KESETARAAN GENDER PENGEMUDI PEREMPUAN TRANSJAKARTA - , RIFQI ADLIAN, Dr. Ambar Widaningrum, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This paper explained about womenâs driver. Jobâs restriction based of sex make woman difficult to get a job. It made womanâs protest to againts workâs equality. And then womanâs protest made phenomenon âcross-genderâs workâ, which woman or man work in job that not suitable with their sex. Driver which identic as manâs job can be done by woman. The thing will be attention in cross-genderâs work is why womanâs driver choose to work as driver in Transjakarta. Then, when woman work at transjakarta, it become a question how far gender issues evolved in PT. BMP. This paper used qualitative research by descriptive qualitativeâs method. Data collection technique used interview and observation. beside of this research, it found that the reason woman work as driver is because of their condition of economic. The difficulty finding a job made womanâs driver work as transjakartaâs driver. People around womanâs driver didnât questioned womanâs job. In driverâs management, genderâs equality has been perceived by womenâs driver not only from another driver but also from manager. That thing can be seen from ability to get access, participation in company, communication between workers, and how far that job can be advantage. However, there are still many thing that considered not equality between womanâs and manâs driver. This paper give suggestion that company mustprovide training and give rest facility for womanâs driver. And then company offer more chance to woman to work as transjakartaâs driver. Keyword: woman, driver, Transjakarta, reason to be driver, gender, equality